2013
DOI: 10.1016/j.biortech.2012.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Sequential accumulation of starch and lipid induced by sulfur deficiency in Chlorella and Parachlorella species

Abstract: The influence of sulfur deficiency on biomass production was analyzed in the four Chlorellaceae species, Chlorella vulgaris, Chlorella sorokiniana, Chlorella lobophora, and Parachlorella kessleri. Culturing under sulfur-deficient conditions promoted transient accumulation of starch followed by a steady increase in lipid storage. Transmission electron microscopy indicated an increase and decrease in starch granules and subsequent enlargement of lipid droplets under sulfur-deficient conditions. Chlorellaceae spp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
58
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 21 publications
9
58
0
3
Order By: Relevance
“…However, after 24 h of stress exposure, FA accumulation was accelerated, and TCH content decreased. Similar behavior has recently been shown in five different Chlorellaceae species, where lipid accumulation followed a reduction in stored starch when exposed to different stresses (13,14). The hypothesis that during the second phase of the stress response (24 -48 or 96 h), starch is degraded to support continuous FA synthesis was supported by our in silico experiments.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, after 24 h of stress exposure, FA accumulation was accelerated, and TCH content decreased. Similar behavior has recently been shown in five different Chlorellaceae species, where lipid accumulation followed a reduction in stored starch when exposed to different stresses (13,14). The hypothesis that during the second phase of the stress response (24 -48 or 96 h), starch is degraded to support continuous FA synthesis was supported by our in silico experiments.…”
Section: Discussionsupporting
confidence: 87%
“…This observation suggests that the FAs are in part built from starch degradation derivatives. Similar results have been obtained in studies of species of the family Chlorellaceae; for instance, under sulfur deficiency, lipid accumulation begins with a reduction in stored starch (13), and in Chlorella UTEX29, the number of lipid bodies increased while starch granules decreased after 24 h of nitrogen deprivation (14). * This work was financially supported by the European Commission's Sev-Several studies have investigated the interplay of FA and CH biosynthesis and its regulation in microalgae, often with the aim of enhancing oil accumulation in the cell (15)(16)(17)(18)(19)(20).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…In Chlorella, there is a tradeoff between the quantities of starch and TAG, and some reports showed that starch accumulates transiently and decreases thereafter (Mizuno et al, 2013;Takeshita et al, 2014), suggesting that the carbon storage starch was used for TAG synthesis. In C. merolae, however, the starch content in cells was maintained while the TAG level increased, at least under our experimental conditions (Fig.…”
Section: Neutral Lipid and Sugar Contents During Culturingmentioning
confidence: 99%
“…Li et al (2010) also reported that the lipid accumulation in a starch-less mutant of C. reinhardtii was enhanced under stress conditions, suggesting that a shift of the carbon flux from starch to TAG biosynthesis in microalgae species may exist. In Chlorella, another green algal species, trade-offs have been observed between the accumulations of starch and lipids (Fernandes et al, 2013;Mizuno et al, 2013), and a clear accumulation shift from starch to lipid has been reported (Bellou and Aggelis, 2012;Takeshita et al, 2014). However, it is not clear whether the same is true in other taxonomic groups of algae.…”
Section: Introductionmentioning
confidence: 99%